Exploration Risk Factors Post Traumatic Stress Disorder in Children as Victims of Sexual Violence - Wahyuni, Hera; Hamidah, Hamidah; Hartini, Nurul; Suryanto, Suryanto (Journal of Educational, Health and Community Psychology, 2018)
This research aimed to explore the risk factors of PTSD in children as victims of sexual violence so as to build the concept of integrative psychological dynamics of PTSD in children as victims of sexual violence in Indonesia and also reveal the impact of PTSD on children as victims of sexual violence. Â Sexual violence is a lifelong crime in which the victim who experienced the incident will experience a prolonged trauma or what is commonly called post traumatic sress disorder (PTSD). PTSD is a mental disorder that can develop after a person is affected by a traumatic event.The method used was qualitative method with case study approac while the data collection technique was done by using in-depth interview and participant observation. The research was conducted on children as victims of sexual violence aged 11 and 12 years old and experienced PTSD. Stages of data analysis were data collection, data reduction, data presentation, conclusion and verification until the final conclusion, through the process of validity, like triangulation data.The results of this research revealed that PTSD risk factors in children as victims of sexual violence are associated with 2 (two) factors such as, : 1) Internal factors or vulnerabilities in children include low intelligence and shyness, introvert, and pessimistic personality, 2) Environmental factors include the lack of support from parents, teachers, friends and people around the victim which triggered the development of PTSD. Children as victims of sexual violence who get PTSD also experience the impact on the function of life, where they are no longer able to perform daily life functions such as going to school, socializing and doing their hobby.